2012
DOI: 10.1186/1756-8722-5-51
|View full text |Cite
|
Sign up to set email alerts
|

Homozygous A polymorphism of the complement C1qA 276 correlates with prolonged overall survival in patients with diffuse large B cell lymphoma treated with R-CHOP

Abstract: BackgroundThe precise mechanism of action for rituximab (R) is not fully elucidated. Besides antibody-dependent cellular cytotoxicity (ADCC), complements may also play an important role in the clinical response to rituximab-based therapy in diffuse large B cell lymphoma (DLBCL). The purpose of this study was to explore the relationship between C1qA[276] polymorphism and the clinical response to standard frontline treatment with R-CHOP in DLBCL patients.MethodsGenotyping for C1qA[276A/G] was done in 164 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Myelosuppression, nausea or vomiting, and liver dysfunction were more frequent than those in CHOP-21 regimen used in aggressive lymphoma [39,40], but much less than those occurring in SMILE study [19]. There was no treatment-related death in this study.…”
Section: Discussionmentioning
confidence: 67%
“…Myelosuppression, nausea or vomiting, and liver dysfunction were more frequent than those in CHOP-21 regimen used in aggressive lymphoma [39,40], but much less than those occurring in SMILE study [19]. There was no treatment-related death in this study.…”
Section: Discussionmentioning
confidence: 67%
“…ADCC) a long time ago (Cartron et al, 2002;Dall'Ozzo et al, 2004), even though correlations were observed in some indications and not in others (Boross and Leusen, 2012;Dornan et al, 2010;Farag et al, 2004). A correlation between a single nucleotide polymorphism (SNP) in the C1qA gene (rs172378, also described as C1qA [276]) with prolonged response rates to rituximab therapy of follicular lymphoma and diffuse large B-cell lymphoma has been described (Jin et al, 2012;Racila et al, 2008). However, as the SNP does not lead to a change in the C1q amino acid composition, the mechanism is poorly understood and this observation therefore does not provide an insight into the contribution of complement in CD20 antibody therapy .…”
Section: Cancermentioning
confidence: 99%
“…Some studies have evidenced variations in clinical responses to rituximab as a single-agent in patients with FL based on C1q gene SNPs, being more effective for carriers of the 276A allele (C1qA [276] ) [58], correlated also with better OS and higher rate of complete responses in a retrospective study with DLBCL patients treated with R-CHOP [59]. However, on the other hand, several groups have ensured that ADCC plays a more important role in the antiproliferative effect of rituximab.…”
Section: Complement Dependent Cytotoxicitymentioning
confidence: 99%